2017
DOI: 10.1037/neu0000382
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of automated eye tracking with the Early Childhood Vigilance Test of attention in younger HIV-exposed Ugandan children.

Abstract: Objective Tobii eye tracking was compared to webcam-based observer scoring on an animation viewing measure of attention (ECVT) to evaluate the feasibility of automating measurement and scoring. Outcomes from both scoring approaches were compared to the Mullen Scales of Early Learning (MSEL), Color-Object Association Test (COAT), and Behavior Rating Inventory of Executive Function for preschool children (BRIEF-P). Method 44 children 44 to 65 months of age were evaluated with the ECVT, COAT, MSEL, and BRIEF-P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…As did Boivin et al (2017) with Ugandan HIV-exposed toddlers and Forssman et al (2017) with Malawian infants, who both used Tobii eye tacking instrumentation and a cognitive visual tracking task, the present study has also established the feasibility of eye tracking measures, only this time with infant children in a medical clinic setting. We also established ways in which the Fagan test, modified for the Ugandan context, produces working memory outcomes that significantly correlated with other cognitive and neurodevelopmental assessments in HIV-affected children in an African context.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…As did Boivin et al (2017) with Ugandan HIV-exposed toddlers and Forssman et al (2017) with Malawian infants, who both used Tobii eye tacking instrumentation and a cognitive visual tracking task, the present study has also established the feasibility of eye tracking measures, only this time with infant children in a medical clinic setting. We also established ways in which the Fagan test, modified for the Ugandan context, produces working memory outcomes that significantly correlated with other cognitive and neurodevelopmental assessments in HIV-affected children in an African context.…”
Section: Discussionmentioning
confidence: 66%
“…The first is a study by our group in which Tobii eye tracking was compared to webcam-based observer scoring on an animation viewing measure of attention (Early Childhood Vigilance Test or ECVT) to evaluate the feasibility of automating Tobii eye tracking measurement and scoring, with the same instrumentation used in the present study (Michael J. Boivin et al, 2017). For HIV-exposed Ugandan children 44 to 65 months from our present study site, Tobii eye tracking measures of gaze length duration for a six minute animation cartoon were compared performance measures from the Mullen Scales of Early Learning (MSEL), Color-Object Association Test (COAT), and Behavior Rating Inventory of Executive Function for preschool children (BRIEF-P).…”
Section: Introductionmentioning
confidence: 99%
“…21 22 The majority of studies examining infant visual orienting by automated eye-tracking come from high-resource laboratories in Western countries, but similar research has recently been expanded to assess visual orienting [23][24][25][26] as well as other aspects of cognition in children in less studied populations in mid-income and low-income countries. [27][28][29] These studies have shown that eyetracking can be performed in low-resource settings, typically at central healthcare facilities, [26][27][28] although the use of a portable system at participants' homes in rural Vanuatu has also been reported. 29 A study conducted in Malawi found no association between eye-tracking measures of visual orienting at 7-9 months and tests of cognitive and motor function at 18 months.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…We have reported how we determined our sample size, all data exclusions (if any), all manipulations, and all measures in the study, and which are described in further detail in a prior study (Boivin, Weiss, et al, 2017) and in the source clinical trial study (Boivin, Nakasujja, et al, 2017). All data, analysis code, and research materials are available upon request to the senior author (MJB) and contingent upon suitable intellectual property agreements with Michigan State University.…”
Section: Transparency and Openness Statementmentioning
confidence: 99%